A 3'-untranslated region (3'UTR) induces organ adhesion by regulating miR-199a* functions. - Daniel Y Lee (Public Library of Science (PLoS), 2009)
Mature microRNAs (miRNAs) are single-stranded RNAs of 18-24 nucleotides that repress post-transcriptional gene expression. However, it is unknown whether the functions of mature miRNAs can be regulated. Here we report that expression of versican 3'UTR induces organ adhesion in transgenic mice by modulating miR-199a* activities. The study was initiated by the hypothesis that the non-coding 3'UTR plays a role in the regulation of miRNA function. Transgenic mice expressing a construct harboring the 3'UTR of versican exhibits the adhesion of organs. Computational analysis indicated that a large number of microRNAs could bind to this fragment potentially including miR-199a*. Expression of versican and fibronectin, two targets of miR-199a*, are up-regulated in transgenic mice, suggesting that the 3'UTR binds and modulates miR-199a* activities, freeing mRNAs of versican and fibronectin from being repressed by miR-199a*. Confirmation of the binding was performed by PCR using mature miR-199a* as a primer and the targeting was performed by luciferase assays. Enhanced adhesion by expression of the 3'UTR was confirmed by in vitro assays. Our results demonstrated that upon arrival in cytoplasm, miRNA activities can be modulated locally by the 3'UTR. Our assay may be developed as sophisticated approaches for studying the mutual regulation of miRNAs and mRNAs in vitro and in vivo. We anticipate that expression of the 3'UTR may be an approach in the development of gene therapy.